La Cour européenne des droits de l’homme - Eissen, Marc-André (Les Cahiers de droit, 1984)
The European Convention for the Protection of Human Rights and Fundamental Freedoms came into force on September 1953. In 1959, the European Court of Human Rights began its work which is to apply the Convention to particular cases. Since then, it has delivered 94 judgments. For Canadian Lawyers, since the Canadian Charter of Rights and Freedoms has come into force, the European Court and its decisions are of particular signifiance. The following article concerns the Court itself, especially the status of its judges. It also concerns the functions, powers and procedures of the Court and lastly relates the spirit with which the Convention has been applied to the National Laws of the Members of the Council of Europe for the past 25 years.